The escalatory Red Queen: Population extinction and replacement following arms race dynamics in poplar rust. Issue 7 (27th January 2017) - Persoons, Antoine; Hayden, Katherine J.; Fabre, Bénédicte; Frey, Pascal; De Mita, Stéphane; Tellier, Aurélien; Halkett, Fabien
Abstract: Host–parasite systems provide convincing examples of Red Queen co‐evolutionary dynamics. Yet, a key process underscored in Van Valen's theory – that arms race dynamics can result in extinction – has never been documented. One reason for this may be that most sampling designs lack the breadth needed to illuminate the rapid pace of adaptation by pathogen populations. In this study, we used a 25‐year temporal sampling to decipher the demographic history of a plant pathogen: the poplar rust fungus, Melampsora larici‐populina . A major adaptive event occurred in 1994 with the breakdown of R7 resistance carried by several poplar cultivars widely planted in Western Europe since 1982. The corresponding virulence rapidly spread in M. larici‐populina populations and nearly reached fixation in northern France, even on susceptible hosts. Using both temporal records of virulence profiles and temporal population genetic data, our analyses revealed that (i) R7 resistance breakdown resulted in the emergence of a unique and homogeneous genetic group, the so‐called cultivated population, which predominated in northern France for about 20 years, (ii) selection for Vir7 individuals brought with it multiple other virulence types via hitchhiking, resulting in an overall increase in the population‐wide number of virulence types and (iii) – above all – the emergence of the cultivated population superseded the initial population which predominated at the same place before R7 resistance breakdown. Our temporal analysis illustrates how antagonistic co‐evolution can lead to population extinction and replacement, hence providing direct evidence for the escalation process which is at the core of Red Queen dynamics.